Sediment and Nutrient Mobility in Terraced Paddy Fields under Traditional Irrigation System - . SUKRISTIYONUBOWO (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2008)
Sediment and nutrient mobility in terraced paddy fields under traditional irrigation system have been investigated in Keji Village, the Semarang District during the Wet Season 2003-2004. The aims were to evaluate the incoming and outgoing sediment and nutrient during rice growth cycle and to study the mobility of sediment and nutrient in the wet season. The treatments included Farmer Practices, Farmer Practices + Rice Straw, Improved Technology, and Improved Technology + Rice Straw. The discharge of irrigation water during puddling was the greatest varying between 2.55 ± 1.23 and 3.10 ± 0.55 l second-1, while during the vegetative phase was the lowest ranging from 0.33 ± 0.15 to 0.54 ± 0.15 l second-1. At the generative stage was about 1.38 ± 0.28 to 1.60 ± 0.06 l second-1. Furthermore, the discharge of suspended sediment during puddling varied between 0.89 ± 0.20 and 1.31 ± 0.34 l second-1, while atvegetative phase was the lowest ranging from 0.21 ± 0.07 to 0.78 ± 0.52 l second-1. At generative stage was about 1.13 ± 0.06 to 1.32 ± 0.09 l second-1. Only during the puddling that the incoming sediment was lower than outgoing sediment. The total amount of deposited sediment varied between 647 and 1,589 kg ha-1 season-1 from the total incoming sediment of 2,715 to 5,521 kg ha-1 season-1. In contrast, the incoming dissolved nutrient (nitrogen, phosphorus and potassium) was trapped in the paddy field areas, varying between 7.20 and 13.62 kg N; 0.13 and0.20 kg P; and from 7.25 to 13.42 kg K ha-1 season-1. There were no significantly different among treatments, both for sediment and nutrient deposited. These results demonstrate that terraced paddy field system is not only place for producing rice, but also providing an environmental services, like nutrient and sediment conserving.